(untitled) (Revista de Ciências Agroveterinárias, 2018)
Canola stands out as an important economic alternative as it is a source for the production of oil for human consumption, and in its use for the production of biodiesel. However mechanized harvesting is an obstacle to the expansion of the cultivation of this brassicaceae that need to be solved. The objective of this work was to evaluate five canola mechanized harvesting management systems, with or without the application of a sealant, compared to losses of preharvest and harvest, grain yield and water content in the grains. The canola hybrid Hyola 61 was used, being seeded with row spacing of 0.45 meters, and density of 40 viable seeds m-2. The treatments resulted from the combination of different management processes combined with a sealant. The adopted managements were: M1- harvesting with cut straight to the natural maturation point (untreated); M2 - previous chemical desiccation with diquat; M3 - previous chemical desiccation with ammonium glufosinate; M4 - cut-windrowing, and M5 - ethefom application. The harvest managements with cut-windrowing, previous chemical desiccation, and applying etefom, singly or in combination to sealant, reduced the grain losses in the harvest allowing higher yields to be obtained, and also reducing the water content in the grains, under conditions of excessive rainfall.